Majmūʿa-yi Rashīdiyya : Shāmil-i Kitābhā-yi Tawḍīḥāt-i Rashīdī, Miftāḥ al-tafāsīr, Sulṭāniyya, Laṭāʾif al-ḥaqāʾiq - Hamadānī, Rashīd al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Rashīd al-Dīn Hamadānī (d. 718/1319) came from a Jewish family in Hamadan. His grandfather had been a courtier of Hūlāgū Khān (r. 1256-65) while his father was a court pharmacist. Rashīd al-Dīn converted to Islam when he was about 30 years old. Trained as a physician, he started his career under the Il-khanid Abāqā Khān (r. 1265-82), rising to the rank of vizier under Ghāzān (r. 1295-1304), Öljeitü (r. 1304-16) and Abū Saʿīd Bahādur Khān (r. 1316-35), who had him executed in 718/1319. Rashīd al-Dīn was also an historian and as such he is best known for his monumental Jāmiʿ al-tawārīkh , the earliest attempt at writing a world history and a major source of information on the emergence and organisation of the Mongol empire. The four treatises published here show another side of Rashīd al-Dīn's talents as a scholar and are mostly about Qurʾān interpretation, prophethood, revelation, miracles, kingship, and notions around virtue and salvation.